The spontaneous insurrection. Argentina. December 2001 - Carrera, Nicolás Iñigo; Cotarelo, Maria Célia (Pontifícia Universidade Católica de São Paulo, 2004)
The authors analyze social struggles in Argentina from the 1990s up to the recent events that overthrew the government of Fernando De La Rua in the midst of an officially declared state of siege. They point to three phases ofstruggle: 1993-1997 (peak of popular mobilization); 1997-1998/9(disappearance of unity in worker struggles); 1999-2001 (new upsurge of social struggles).